2010
DOI: 10.1007/s00432-010-0937-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metastasis-associated breast cancer genes using a high-resolution whole genome profiling approach

Abstract: Metastasizing tumors had a higher rate of deletions, suggesting possible inactivation of metastasis suppressor genes. We provide preliminary evidence that TSPAN1 may be another important breast cancer suppressor gene belonging to the tetraspanin superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…This did not identify any tumor types with recurrent chromosomal losses involving the SCCRO3 locus at 16p12.3 (32)(33)(34). The absence of chromosomal losses at 16p12.3 was validated by our analysis of results from array comparative genomic hybridization and/or single-nucleotide polymorphism investigations performed on thyroid, head and neck, lung, and neuroendocrine tumors at our institution (data not shown).…”
Section: Sccro3 Expression Is Decreased In Human Tumors-wementioning
confidence: 59%
“…This did not identify any tumor types with recurrent chromosomal losses involving the SCCRO3 locus at 16p12.3 (32)(33)(34). The absence of chromosomal losses at 16p12.3 was validated by our analysis of results from array comparative genomic hybridization and/or single-nucleotide polymorphism investigations performed on thyroid, head and neck, lung, and neuroendocrine tumors at our institution (data not shown).…”
Section: Sccro3 Expression Is Decreased In Human Tumors-wementioning
confidence: 59%
“…We find TSPAN1 expression in prostate cancer is biphasic, with upregulation at the primary site and downregulation in metastatic lesions. Similarly, a study in breast cancer has shown that although TSPAN1 is upregulated in most primary tumours it is more likely to be downregulated in metastatic lesions 72 .…”
Section: Discussionmentioning
confidence: 94%
“…A few studies have shown that primary tumors and their metastases generally share similar copy number aberrations (12,13) and gene expression profiles (14,15), but these studies were underpowered by the scarcity of metastatic biopsies, limiting the identification of differences between these matched tumor pairs. By using experimental mouse models and a limited series of clinical metastatic biopsies, genes associated with the propensity of breast cancer relapse to the bone (16), lung (17,18), and brain (19) have been published.…”
Section: Introductionmentioning
confidence: 99%